2021
DOI: 10.1038/s41598-021-87489-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of heart rate variability estimated with reflective wrist-PPG in elderly vascular patients

Abstract: Optical heart rate monitoring (OHR) with reflective wrist photoplethysmography is a technique mainly used in the wellness application domain for monitoring heart rate levels during exercise. In the absence of motion, OHR technique is also able to estimate individual beat-to-beat intervals relatively well and can therefore also be used, for example, in monitoring of cardiac arrhythmias, stress, or sleep quality through heart rate variability (HRV) analysis. HRV analysis has also potential in monitoring the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…In addition, the relative error of SD1 is larger than SD2. These results support the results obtained in the literatures [15,20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the relative error of SD1 is larger than SD2. These results support the results obtained in the literatures [15,20].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, PPI is also widely used to obtain heart rate in wearable sensors instead of RRI, because it is easier to measure in daily life. However, Reference [15] states that the PPI increases relative error of some of the indices such as LF/HF and SD1/SD2. Reference [20] also shows that the use of PPI increases the error of HF and SD1.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Bent and Dunn plan to include recordings under physical activity, and thus variable signal quality in future works [28]. Our own previous work has also shown that signal quality of PPG recorded from patients using wearable devices is quite volatile, and the quality of PRV derivation highly depends on both the specific PRV parameter and the individual patient [39]. However, none of the comparable works did systematically consider SNR so far.…”
Section: Main Findings and Relation To Other Workmentioning
confidence: 99%
“…The standard deviation of the NN intervals (SDNN) [7] was also calculated. Note that popular features such as RMSSD [7] and LF/HF ratio [7] were not considered as they are particularly noisy when computed from a PPG signal [15]. Consequently, the feature set extracted for the HRV is as follows:…”
Section: Heart Rate Variability Feature Setmentioning
confidence: 99%